The Effect of Liquidity and Profitability on Company Value (In Food and Beverage Sector Companies Listed on the IDX IN 20202024) - Rasam, Fadli; Interdiana Candra Sari, Ani; Rozali, Muhammad (Cv. Syntax Corporation Indonesia, 2025)
This study aims to determine the influence of liquidity and profitability on the value of companies in the food and beverage sector listed on the IDX in 2020–2024. The research method used is quantitative. The research population is food and beverage sector companies listed on the Indonesia Stock Exchange with an observation period of 2020–2024 totaling 10 companies and a sample of 50 sample data. This researcher uses documentation techniques and the data source is secondary data, namely data on liquidity, profitability, and company value in food and beverage sector companies listed on the IDX in 2020–2024. The researcher used the normality test, linearity test, autocorrelation test, heteroscedasticity test, multicollinearity test, t-test using the SPSS Version 20 program. The results show that there is a significant influence of Current Ratio (CR) and Return on Assets (ROA) on Company Value (NP). The implication of the results of the research for companies is that companies must continue to maintain good liquidity and profitability to increase the company's value. The company's management must pay attention to financial factors such as liquidity and profitability, even in unstable economic conditions.